Highly efficient magnetic chicken bone biochar for removal of tetracycline and fluorescent dye from wastewater: Two-stage adsorber analysis - Oladipo, Akeem Adeyemi; Ifebajo, Ayodeji Olugbenga (Academic Press Ltd- Elsevier Science Ltd, 2018)
Magnetic chicken bone biochar (MCB) was fabricated and characterised. The specific surface area, magnetisation value and pH(pzc) of the MCB were found to be 328 m(2) g(-1), 64.7 emu/g and 8.3 respectively. The adsorptive performance of MCB for rhodamine B dye (RB) and tetracycline (TC) removal in a single and two-stage stirred adsorber (TSA) was evaluated. The TSA reduced the pressure drops, mass transfer resistances, and fouling of the adsorbent. 63.0 g MCB is required to remove 75% of RB and TC in a single stage system within 12 h. However, the optimised TSA confirmed that 33.2 g of MCB is needed to achieve 96% removal of TC and 22.2 g for RB within 180 min of 100 mgL(-1) effluent solutions. The sorption was suitably described by the Freundlich mechanism. Based on the comparative performance, the MCB is considered a viable efficient and magnetically separable alternative adsorbent. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Magnetic bone biochar; Two-stage stirred adsorber; Azo dyes; Tetracycline; Adsorption; Waste management